2021
DOI: 10.3233/cbm-203075
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNAs as potential biomarkers for osimertinib resistance of non-small cell lung cancer patients

Abstract: BACKGROUND: Osimertinib is an epidermal growth factor receptor-tyrosine kinase inhibitor that specifically targets the T790M mutation in cancer.Unfortunately, most non-small cell lung cancer (NSCLC) patients develop osimertinib resistance. Currently, the molecular biomarkers for monitoring osimertinib resistance are not available. OBJECTIVE: This study aimed to examine the profile of exosomal miRNA in the plasma of osimertinib-resistant NSCLC patients. METHODS: Plasma exosomal miRNA profiles of 8 NSCLC patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…In addition, Li et al [85] showed that plasma exosomal miR-92b-3p was significantly increased in chemoresistant small cell lung cancer patients and might serve as a potential dynamic biomarker for monitoring the drug resistance. Exosomal miR-29a-3p and miR-150-5p were identified as circulating biomarkers during thoracic radiation therapy for NSCLC and were correlated with delivered radiation therapy dose [86] . At present, precision medicine based on immunotherapy and targeted therapy has given new hope for lung cancer patients.…”
Section: Texs Serve As Diagnostic and Prognostic Biomarkers In Lung C...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Li et al [85] showed that plasma exosomal miR-92b-3p was significantly increased in chemoresistant small cell lung cancer patients and might serve as a potential dynamic biomarker for monitoring the drug resistance. Exosomal miR-29a-3p and miR-150-5p were identified as circulating biomarkers during thoracic radiation therapy for NSCLC and were correlated with delivered radiation therapy dose [86] . At present, precision medicine based on immunotherapy and targeted therapy has given new hope for lung cancer patients.…”
Section: Texs Serve As Diagnostic and Prognostic Biomarkers In Lung C...mentioning
confidence: 99%
“…The ensuing problems of drug resistance have gained much interest from the research community. For example, exosomal miR-323-3p, miR-1468-3p, miR-5189-5p, and miR-6513-5p were identified as potential biomarkers to discriminate between osimertinib-resistant and osimertinib-sensitive NSCLC patients [ 87 ] , and exosomal miR-210-3p secreted by osimertinib-resistant HCC827 and PC-9 cells was able to promote epithelial-mesenchymal transition and drug resistance in osimertinib-sensitive, EGFR mutant NSCLC cells [ 88 ] . Moreover, exosomal circRNA_102481 enhanced EGFR-TKIs resistance through the microRNA-30a-5p/ROR1 axis in NSCLC [ 89 ] .…”
Section: Texs Serve As Diagnostic and Prognostic Biomarkers In Lung C...mentioning
confidence: 99%
“…In this regard, some examples of lung, prostate, and breast cancers will be described. Janpipatkul et al analyzed the vesicular miRNA profile of eight patients affected by non-small-cell lung cancer (NSCLS) [ 161 ]. The patients were diagnosed with advanced NSCLC with EGFR mutations and started treatment with osimertinib.…”
Section: Extracellular Vesicles As a Tool To Monitor Chemoresistancementioning
confidence: 99%
“…The patients were diagnosed with advanced NSCLC with EGFR mutations and started treatment with osimertinib. This drug is a third-generation inhibitor targeting the epidermal growth factor receptor tyrosine kinase (EGFR); it is used to treat a subgroup of NSCLS patients harboring the T790M-EGFR mutation [ 161 ]. It is reported that resistance could appear after 9–13 months of treatment [ 162 ].…”
Section: Extracellular Vesicles As a Tool To Monitor Chemoresistancementioning
confidence: 99%
See 1 more Smart Citation